Jenis dan Unsur Penentu Makna Dalam Kajian Semantik (Ad-Dilalah) - Salsabila Rizma; Agustiar Agustiar (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The study of the meaning of words in a particular language according to the semantic classification system is a branch of linguistics whose task is solely to examine the meaning of words, their origins, even how they developed, and the reasons for changes in meaning in the history of language. Many other fields of science are related to semantics, therefore meaning plays a role depending on the use of language as a tool for conveying mental experiences, thoughts and intentions in society. The field of semantics is limited to efforts to pay attention to and study the process of transposition of word meanings in language use. Ullman (1972) argues, if someone thinks about the meaning of a word, they simultaneously think about its reference or vice versa. The relationship between two things, meaning and words, is where meaning is born.